THE IMPACT OF INFOGRAPHICS IN AN ONLINE JIGSAW SETTING TOWARDS INDONESIAN EFL LEARNERS’ READING COMPREHENSION - Made Trisna Cahyani; I Putu Ngurah Wage Myartawan; I Nyoman Pasek Hadi Saputra (Universitas Pendidikan Ganesha, 2021)
This study aimed to investigate the impact of infographics in online Jigsaw setting towards Indonesian EFL senior high school students’ reading comprehension. The research was a pre-experimental study with one group pretest-posttest design. The sample was one class of intact groups from tenth graders which was randomly assigned by English teacher in SMA Negeri 1 Singaraja. The data collection employed pre-test-posttest and were analyzed descriptively and inferentially through IBM SPSS Statistics 23. The results show that (1) the students’ posttest mean was 88.38 which was higher than the pretest that was 65.00; and (2) there was a significant difference between the posttest mean and that pretest mean Sig. (two-tailed) was 0.000, which was < 0.05. Therefore, it could be concluded that infographics in an online Jigsaw setting had a positive and significant impact towards Indonesian EFL’s reading comprehension.